Nutrient removal (Water Environment Federation, 2010)
This Water Environment Federation resource provides comprehensive information on biological and chemical methods for nitrogen and phosphorus removal from wastewater. This book covers environmental and regulatory issues and provides an integrated approach for combined nitrogen and phosphorus removal, including details on ammonia and dewatering liquors treatment. Natural treatment systems are also discussed in this definitive guide.
Keywords: Sewage -- Purification -- Nutrient removal.; Sewage -- Purification -- Nitrogen removal.; Sewage -- Purification -- Phosphate removal.; elektronické knihy; electronic books